Nutritional Evaluation Of Mealworms From Poly(3-Hydroxybutyrate) Recovery And Its Potential Application As Aquaculture Feed Ingredient - Idris, Zainab Ladidi (2019)
Polyhydroxyalkanoates (PHAs) are interesting bio-based polymers to replace some petrochemical plastics. To date, the selling price of PHA is high due in part to the costly downstream processes in PHA production. Furthermore, the non-PHA part of the bacterial cells which is nutritive, is lost during the PHA recovery process. High cell density cultures of Cupriavidus necator H16 (161 g/L cell dry weight) and an improved biological recovery method of PHA by using mealworms (Tenebrio molitor), were established. Freeze-dried washed and unwashed cells containing 70 ± 2.0 wt% P(3HB) were fed to mealworms at 12.5% of their body weight (125 g of cell/ 1kg of mealworms). Washed cells was more palatable and consumed daily due to its lower content of mineral salts compared to the alternate days consumption of unwashed cells.